The Role of the Nagari Government in the Revitalization of BUMNAG Tigo Sapilin Management in Nagari Tambangan, Tanah Datar Regency - Utari, Rima; Akmal, Artha Dini (TOFEDU: The Future of Education Journal, 2025)
This research delves into the function of the Nagari Government in rejuvenating the operations of BUMNag Tigo Sapilin, located in Nagari Tambangan, Tanah Datar Regency. These restorative actions were prompted by a standstill in management and the weakening of BUMNag’s accomplishments, which in turn impacted its economic input to the area. The purpose of this investigation is to depict the ways in which the Nagari Government undertakes its duties as a controller, enabler, and energizer, and also to pinpoint the difficulties experienced throughout the recovery process. Employing a qualitative research method, the gathering of information was achieved through conversations, monitoring, and the review of relevant paperwork. The results indicate that the Nagari Government has successfully executed its duties as a controller and energizer, demonstrated by actions such as creating rules and giving inspiration to the managerial staff. Nevertheless, its enabling role has not been fully realized, given that the Nagari Government has neglected to organize educational sessions or development opportunities for the newly designated BUMNag leaders. The difficulties encountered encompass both internal aspects and external elements, a scarcity of personnel, insufficient backing from the public, and restrictions on financial resources. The study determines that increasingly cohesive and enduring plans, which include developmental courses, guidance, and reinforcing public support, are required to guarantee the efficiency of BUMNag’s managerial renewal and to improve its impact on the well-being of the community.